Development and internal validation of a simple clinical score for the estimation of the probability of deep vein thrombosis in outpatient emergency department patients - Thor-David Halstensen; Camilla Hardeland; Waleed Ghanima; Vigdis Abrahamsen Grøndahl; Aliaksandr Hubin; Mazdak Tavoly (Research and Practice in Thrombosis and Haemostasis)
Background: Wells score comprises subjective elements, making physicians reluctant to use Wells score or cause them to use it incorrectly. Objectives: To develop and internally validate a prediction score that is objective and simple for evaluating suspected deep vein thrombosis (DVT), with a safety comparable with that of Wells score. Methods: We performed a post hoc analysis using data from the Ri-Schedule study (NCT02486445) involving suspected DVT patients at Østfold Hospital’s Emergency Department, Norway (2015-2018). Candidate variables were identified through bootstrapping technique, with a confirmed DVT diagnosis as the outcome variable. Sensitivity, specificity, negative predictive value (NPV), and positive predictive values (PPV) were estimated and compared with the 2-tier Wells score. Results: Among 1312 patients (median age, 64 years [IQR, 52-73]; 55% women), 19.9% were diagnosed with DVT. Exploration of 30 variables identified tenderness along deep veins and previous venous thromboembolism as significant predictors (selection frequency >60% in 1000 bootstrapping samples). The derived score categorized 450 patients with 0 items as unlikely to have DVT, of whom 8.0% were diagnosed with DVT, compared with 8.2% in DVT unlikely category according to Wells score. Compared with Wells score, the derived score demonstrated sensitivity of 86.2 (95% CI, 81.4-90.2) vs 80.1 (95% CI, 74.7-84.8), specificity of 39.4 (95% CI, 36.4-42.4) vs 55.3 (95% CI, 52.2-58.3), NPV of 92.0 (95% CI, 89.4-94.0) vs 91.8 (95% CI, 89.7-93.5), and PPV of 26.1 (95% CI, 24.8-27.5) vs 30.8 (95% CI, 28.9-32.8). When incorporating D-dimer cutoff of <0.5 µg/mL, the derived score had sensitivity of 99.6 (95% CI, 97.9-99.9), specificity of 16.1 (95% CI, 13.1-18.4), NPV of 99.4 (95% CI, 96.0-99.9), and PPV of 22.8 (95% CI, 22.3-23.3). Conclusion: The derived DVT score, with 2 objective variables, had a comparable safety with that of the Wells score. However, an external validation is mandated prior to clinical use.